Effects of Strike Participation on the Political Consciousness of Canadian Postal Workers - Langford, Tom (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
Marxists have long argued that major strikes produce an explosion of workers' class consciousness. This article discusses some weaknesses of the explosion-of-consciousness thesis, and tests research hypotheses using data from a case study of the 1987 strike by the Hamilton local of the Canadian Union of Postal Workers. A major finding is that an increase in a postal worker's negative attitudes toward out-groups did not necessarily go hand in hand with an increase in that striker's positive identifications with in-groups such as fellow workers, the local union and the labour movement. This supports treating the in-group and out-group dimensions of class consciousness as distinct. A second finding supports the hypothesis that an explosion of in-group consciousness due to inter-group conflict is more likely to occur among workers who are already identified with the in-group.